Keeping your armour intact: How HIV-1 evades detection by the innate immune system: HIV-1 capsid controls detection of reverse transcription products by the cytosolic DNA sensor cGAS Prospects and Overviews J. Maelfait et al. - Maelfait, J; Seiradake, E; Rehwinkel, J (John Wiley and Sons Inc., 2014)
HIV-1 infects dendritic cells (DCs) without triggering an effective innate antiviral immune response. As a consequence, the induction of adaptive immune responses controlling virus spread is limited. In a recent issue of Immunity, Lahaye and colleagues show that intricate interactions of HIV capsid with the cellular cofactor cyclophilin A (CypA) control infection and innate immune activation in DCs. Manipulation of HIV-1 capsid to increase its affinity for CypA results in reduced virus infectivity and facilitates access of the cytosolic DNA sensor cGAS to reverse transcribed DNA. This in turn induces a strong host response. Here, we discuss these findings in the context of recent developments in innate immunity and consider the implications for disease control and vaccine design. © 2014 The Authors.